Transformative law and public policy - Govindjee, Avinash; Mathew, Babu; Narrain, Arvind; Pellissery, Sony (London Routledge, 2020)
This book explores the convergence of law and public policy. Drawing on case studies from Asia, Europe, the Middle East and Australia, it examines how judicial and political institutions are closely linked to the socio-economic concerns of the citizens. The essays argue for the utilisation of both legislative and executive, private and public spheres of society as vehicles for transformative social change and to safeguard against violations of socio-economic rights. The volume will be of great interest to both public and private stakeholders, as well as professionals, including NGOs and think tanks, working in the areas of law, government, and public policy. It will also be immensely useful to academics and researchers of constitutionalism, policymaking and policy integration, social justice and minority rights.
Why is law central to policy processes in Global South? / Babu Mathew, Sony Pellissery and Arvind Narrain -- The rise of an anti-global doctrine and strikes in public services / Lilach Litor -- Scrutiny of Sovereign Border Policy for 'Operational Matters' : A New Political Role for an Old Legal Dichotomy in Australia? / Suzanne Bevacqua and John Bevacqua -- Sovereign Debt Restructuring : Locating Indian Law and Jurisprudence in the Contemporary International Legal Order / Ansari Salamah -- The Legal and Policy Questions in Foreign Direct Investment : An Assessment using Indian Case / Priya Misra and Praveen Tripathi -- Politics of Making and Unmaking of the Indian Planning Commission : Destiny of non-statutory institutions / Sony Pellissery, S. Sharada and Anusha Chaitanya -- Constitutional Promise vs Practices of Participation and Representation of Minorities in South Asia / Mushtaq Malla -- Growing up in families with low income : the state's legal obligation to recognize the child's right to adequate standard of living / Julia Köhler-Olsen -- Implementers of law or policymakers too? : A study of street-level bureaucracy in India / Amrutha Jose Pampackal -- Production of space in Urban India : Legal and Policy challenges of land assembly / Varun Panickar -- Rawls, Nozick and Dworkin in an Indian village : Land alienation and multiple versions of distributive justice / Naivedya Parakkal, Sony Pellissery and Rajesh Sampath -- Concluding Reflections : Transformative Constitutionalism as a framework for law and policy integration in the global south / Avinash Govindjee
Includes bibliographical references and index.
Keywords: Public policy (Law) -- Congresses; Law -- Social aspects -- Congresses; Public policy (Law) -- India -- Congresses; Law -- Social aspects -- India -- Congresses